The role of bioprotectants for disease control in integrated crop protection approaches - Köhl, Jürgen (Burleigh Dodds Series in Agricultural Science, 2022)
Bioprotectants have the potential to replace chemical pesticides in agricultural cropping systems and crop protection approaches. Development of new bioprotectants in combination with more restricted use of chemical crop protection will result in their much stronger market position in the future. Bioprotectants fulfil particular roles in current and future crop protection approaches, primarily reducing pesticide residues in harvested products in conventional systems, as well as being the first and preferred control option in integrated pest management programs and organic farming, and complementing resident microbiomes in future resilient cropping systems. The process of developing bioprotectants can take ten to 15 years. This chapter aims to give a brief overview of the role of bioprotectants in current and future crop protection approaches to stimulate discussion within the biocontrol industries, and amongst scientists and funding agencies on the need for new generations of bioprotectants for an agriculture industry undergoing transition.